STRATEGI KOMUNIKASI DALAM IMPLEMENTASI SISTEM INFORMASI MANAJEMEN RUMAH SAKIT ONLINE DI RSUD PROF. DR. MARGONO SOEKARJO - Dewi Pratesya Aulia Wardhani; Mohamad Syahriar Sugandi (Jurusan Manajemen Fakultas Ekonomi dan Bisnis, 2021)
Prof. Dr. Margono Soekarjo Hospital (RSMS) is a Hospital in Purwokerto that developed an innovation of a hospital information system called RSMS Online to improve their health services to patients. The objective of this study was to determine the communication strategy in the implementation of RSMS Online. A theoretical approach from the diffusion of innovation and communication planning was used to determine pre-implementation, implementation, and post-implementation stages. This research used a single case study method. The data was collected through direct observation, interviews, and documentation. The results revealed that the communication strategy in implementing RSMS online consists of three stages: pre-implementation, implementation, and post-implementation. The implementation of RSMS Online provides benefits for patients and the RSMS Hospital. The supporting factors that reinforce the implementation of RSMS Online are the commitment of all employees, human resource skills, technology and information support, provision of information facilities and public computer equipment, and access to internet networks. Meanwhile, the diversity of patient backgrounds and limitations of patients who have devices to access the online system and internet quota are the barriers that impede the implementation of RSMS Online. Keywords: Hospital Information System, Implementation, Socialization